Shifting Of Students' Learning Habits During The Pandemic: The Result From Students And Teachers Perspective - Fadhillah Wiandari; Cut Intan Meutia (Smart Education, 2023)
Abstract: The Covid-19 pandemic has altered practically every aspect of the educational system. The habit, and perhaps the culture, of learning had shifted. This study examines how students' and teachers' habits change during a pandemic. This study aims to determine the impacts of the pandemic on students' studying habits and how well they did in the English course from the perspective of both students and teachers. The research methodology for this study is qualitative descriptive. Surveys and interviews are used to collect data on the impact of students' changing learning patterns during the epidemic on their performance in English class. The data show that kids' learning habits regarding regularity, discipline, and attentiveness are changing.Keywords: learning habits; pandemic; learning outcomes; shifting.